California County Planning Commissioners Conference at Fresno Airport Holiday Inn - Watkins, Howard::::::::: (1982)
Entertainment by Good Company Players' Junior Company: Troy Loftus, Joel Abels, Heidi Blickenstaff, ??, Cathy Lang, Alison McDonald, Stefi Takahaski, Barry Ramalho; Kneeling: Heidi Blickenstaff